PENGARUH KUALITAS PELAYANAN DAN KEPATUHAN BAYAR PAJAK KENDARAAN PRIBADI TERHADAP KEPUASAN PELAYANAN - Hendra Hadiwijaya (International Journal of Social Science and Business, 2017)
Influence Service Quality And Compliance Pay Private Vehicle Tax Service Satisfaction. This study aims to determine and analyze the magnitude of the influence of Service Quality and Compliance Pay Private Vehicle tax partially and simultaneously to Satisfaction Satisfaction Personal Vehicle Tax Service at UPTD Palembang Regional Revenue Office of South Sumatra Province. Methods of data analysis using multiple regression analysis with SPSS program assistance (Statistics for Product and ServiceSolution). The results showed that the Quality of Service and Compliance Pay Private Vehicle tax significantly partially and simultaneously affect Service Satisfaction. Quality of Service dominant influence on Satisfaction Satisfaction Personal Vehicle Tax Service at UPTD Palembang Regional Revenue Service of South Sumatra Province.